The Influence of Teamwork and Organizational Commitment on The Performance of Bri Bank Employees at The Lancang Kuning Branch Office - Sudaryatmo; Andi Mansur Sandrang; H. Mustaqim (Citakonsultindo, 2023)
The performance of employees in a company must always be considered because it is one of the most important factors that determines whether a company can survive in the competition faced by the company. Employees who perform well in a company will advance the company, whereas employees who perform poorly will have an adverse effect on the company and even threaten not to be able to compete with other companies. Achievement of organizational goals is also the goal of banking companies. One of the banking companies in Pekanbaru is Bank Rakyat Indonesia (BRI). This study aims to determine the effect of teamwork and commitment to the performance of back office employees at the BRI Lancang Kuning branch office. The sample is the back office employee of BRI Lancang Kuning Pekanbaru. The method of determining the sample is simple random sampling so that the sample used is 67 back office employees. The data analysis technique used is validity test, reliability test, classic assumption test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and the coefficient of determination. The research results conclude that teamwork and commitment to performance affect the performance of BRI Lancang Kuning Branch employees. This can be proven from the results obtained from the results of the regression coefficient which shows that the magnitude of the influence of the independent variables on the dependent variable which can be explained by this equation model is 74%. This shows that the influence of teamwork and organizational commitment variables on employee performance which can be explained by this equation model is 74% and the remaining 26% is influenced by other factors not included in this regression model such as career paths, communication, awards and others. Based on the t test, the results obtained are tcount (4.427) > ttable (1.996) or sig. 0.000 < 0.05. This means that teamwork has a significant effect on employee performance. And based on the t test, the results obtained are tcount (2,283) > ttable (1,996) or sig. 0.026 <0.05. This means that organizational commitment has a significant effect on employee performance. It can be concluded that this study shows that teamwork and commitment affect the performance of BRI Lancang Kuning employees.